RELATIONSHIP BETWEEN KNOWLEDGE LEVELS AND ATTITUDES WITH ADHERENCE TO ANTIRETROVIRAL (ARV) THERAPY OF HIV/AIDS PATIENTS IN RSUP Dr. KARIADI, SEMARANG - Ginitri, Arumdipta; Annisaa', Eva; Wulandari, Fitri (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2026)
Background: Antiretrovirals (ARV) are drugs that People Living with HIV/AIDS (PLWHA) take to enhance quality of life. Therapy adherence (>95%) is required to attain virologic suppression, prevent resistance, therapy failure, and death. Factors affecting adherence are the level of knowledge and attitude. Objective: This study aims to identify the relationship between knowledge level and attitude with adherence to ARV therapy of HIV/AIDS patients at RSUP Dr. Kariadi, Semarang. Methods: Analytical observational research with cross-sectional design using questionnaires, sampling method using purposive sampling. Adherence questionnaire using MARS-5, knowledge and attitude questionnaires were developed by the researcher, and validity and reliability tests were carried out. Univariate analysis using frequency distribution table, and bivariate analysis using Chi-Square test. Results: The level of knowledge of respondents was good at 88.30%, and poor at 11.70%. The attitude was good at 96.81%, and poor at 3.19%. The compliance was high at 65.96%, and low at 34.04%. A significant association was observed between the level of knowledge (p = 0.028) and attitude (p = 0.014) with adherence to ARV therapy. Conclusion: The majority of HIV/AIDS patients at RSUP Dr. Kariadi, Semarang, who received ARVs, the knowledge level was good, the attitude was good, and the adherence was high. There is a relationship between the level of knowledge and attitude with adherence to ARV therapy of HIV/AIDS patients at RSUP Dr. Kariadi, Semarang.